European Health Data Space-An Opportunity Now to Grasp the Future of Data-Driven Healthcare - Horgan, Denis; Hajduch, Marian; Vrana, Marilena; Soderberg, Jeannette; Hughes, Nigel; Omar, Muhammad Imran; Lal, Jonathan A; Kozaric, Marta; Cascini, Fidelia; Thaler, Verena; Solà-Morales, Oriol; Romão, Mário; et al. (Healthcare (Basel, Switzerland), 2022)
The May 2022 proposal from the European commission for a 'European health data space' envisages advantages for health from exploiting the growing mass of health data in Europe. However, key stakeholders have identified aspects that demand clarification to ensure success. Data will need to be freed from traditional silos to flow more easily and to cross artificial borders. Wide engagement will be necessary among healthcare professionals, researchers, and the patients and citizens that stand to gain the most but whose trust must be won if they are to allow use or transfer of their data. This paper aims to alert the wider scientific community to the impact the ongoing discussions among lawmakers will have. Based on the literature and the consensus findings of an expert multistakeholder panel organised by the European Alliance for Personalised Medicine (EAPM) in June 2022, it highlights the key issues at the intersection of science and policy, and the potential implications for health research for years, perhaps decades, to come.
Keywords: health policy; treatment; access to data; European; EU values; policy framework; data protection; healthcare; space; governance; prevention; diagnosis; data; personalised medicine; health